BİZANS’IN BÜYÜK ROMA’YI YENİDEN KURMA İDEALİ VE İTALYA-SİCİLYA SİYASETİ - Şahin, Seyhun (Fırat University, 2013)
Bizans İmparatorluğu’nda gerek halk gerekse de imparatorlar kendilerini Büyük Roma’nın mirasçıları olarak kabul etmişlerdi. Bu nedenle Büyük Roma’yı tekrar canlandırmak ve eski gücüne kavuşturma fikrine daima inandılar

Both the public and the emperors in the Byzantine Empire, had accepted themselves as heirs of the Great Roman Empire. Because they believed the idea they would to revive the Great Roman Empire and te ideal about it would be powerful as old days
The Politics of Italy-Sicily and the Ideal of Byzantine About Re- Establishment the Great Rome